2016
DOI: 10.1111/zph.12322
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Occupational Brucellosis at a Pharmaceutical Factory in Southeast China

Abstract: Brucellosis is an occupational disease affecting workers in butcher shops, the milking and dairy product industry, causing more than 500 000 new cases around the world. As a national statutory B infectious disease in China, morbidity of brucellosis is rapidly increasing in recent years. We report an occupational outbreak of brucellosis infection in a pharmaceutical factory. Exposure was a result of manual operation in the process line, close contact with sheep placentas, insufficient disinfection and repeated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The proportion of students is second only to that of farmers and herdsmen, Mongolian boys have the custom of playing with lambs, which may increase their risk of infection. Moreover, some brucellosis cases were reported in administrative cadres and teachers, who was non-occupational population for brucellosis; this suggests that brucellosis in this region has an expansive trend from farmers and herdsmen to non-occupational, which may be related to changes in livestock infected transfer and dietary structure [28]. Similarly, a study from Iran showed that most patients lived in rural areas, and that 20.8% (17.4-24.2%) of the patients were ranchers and farmers, 16.9% (14.5-19.4%) were students, and 31.6% (27.0-36.2%) were housewives [29].…”
Section: Discussionmentioning
confidence: 98%
“…The proportion of students is second only to that of farmers and herdsmen, Mongolian boys have the custom of playing with lambs, which may increase their risk of infection. Moreover, some brucellosis cases were reported in administrative cadres and teachers, who was non-occupational population for brucellosis; this suggests that brucellosis in this region has an expansive trend from farmers and herdsmen to non-occupational, which may be related to changes in livestock infected transfer and dietary structure [28]. Similarly, a study from Iran showed that most patients lived in rural areas, and that 20.8% (17.4-24.2%) of the patients were ranchers and farmers, 16.9% (14.5-19.4%) were students, and 31.6% (27.0-36.2%) were housewives [29].…”
Section: Discussionmentioning
confidence: 98%
“…A total of 292 individuals working in slaughterhouses were described as brucellosis-positive in fourteen articles [19,20,23,33,34,[41][42][43][44][45][46][47][48][49]. Most of those individuals were from America (n = 162), Africa (n = 60), and Europe (n = 37) and the minority from Asia (n = 33).…”
Section: Abattoir Workersmentioning
confidence: 99%
“…The main type of pathogen exposure reported was contact with animal fluids, aborted fetus, placenta and viscera. Accidental contact with those materials was described in three studies: in Spain and Ethiopia, 12.26% (13/106) and 48.72% (76/156) of slaughterhouse workers, respectively, reported cutting themselves with dirty sharp blades [45,46], and in China, 100.00% (3/3) of pharmaceutical employees, who worked processing sheep placenta, reported having splashed animal fluids on their faces [47]. The great occurrence of direct contact with biological contaminated fluids aroused the interest of several authors to understand which PPE were used or not by this group of professionals (Table 2).…”
Section: Abattoir Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…And B. abortus which infects cattle is the most frequent in brucellosis of the world. Brucella leads to infertility and abortion in infected animals and causes signi cant economic losses [5]. Human infection with brucellosis is usually accompanied by chronic complications resulting from consumption of unpasteurized dairy products and uncooked meat or direct contact with tissues of infected animals.…”
Section: Introductionmentioning
confidence: 99%